Vitamin D deficiency and its relationship with cardiac iron and function in patients with transfusion-dependent thalassemia at Chiang Mai University Hospital - Prapai Dejkhamron (2018)
© 2018 Taylor & Francis Group, LLC. Background: Vitamin D deficiency is common in patients with thalassemia. Vitamin D deficiency could be related to cardiac dysfunction. Increased parathyroid hormone (PTH) is also known to be associated with heart failure. Objectives: To determine the prevalence of Vitamin D deficiency and to explore the impact of Vitamin D deficiency on cardiac iron and function in patients with transfusion-dependent thalassemia. Method: A cross-sectional study in patients with Transfusion-dependent thalassemia was conducted. Patients with liver disease, renal disease, type 1 diabetes, malabsorption, hypercortisolism, malignancy, and contraindication for MRI were excluded. Calcium, phosphate, PTH, vitamin D-25OH were measured. CardiacT2*and liver iron concentration (LIC) and left ventricular ejection fraction (LVEF) were determined. Results Sixty-one (33M/28F) patients with Transfusion-dependent thalassemia were enrolled. The prevalence of Vitamin D deficiency was 50.8%. Patients with cardiac siderosis had tendency for lower D-25OH than those without siderosis (15.9 (11.7–20.0) vs. 20.2 (15.85–22.3) ng/mL); p = 0.06). Serum calcium, phosphate, PTH, LIC, cardiac T2*, and LVEF were not different between the groups with or without Vitamin D deficiency. Patients with Vitamin D deficiency had significantly lower hemoglobin levels compared to those without Vitamin D deficiency (7.5 (6.93–8.33) vs. 8.1 (7.30–8.50) g/dL; p = 0.04). The median hemoglobin in the last 12 months was significantly correlated with D-25OH. Cardiac T2*had significant correlation with PTH. Conclusion: Vitamin D deficiency is prevalent in patients with Transfusion-dependent thalassemia. Vitamin D level is correlated with hemoglobin level. Vitamin D status should be routinely assessed in these patients. Low PTH is correlated with increased cardiac iron. This study did not demonstrate an association between Vitamin D deficiency and cardiac iron or function in patients with Transfusion-dependent thalassemia.